GAMBARAN HISTOLOGIS LIMFA (LIEN) SETELAH PAPARAN MADU PADA TIKUS PUTIH (RATTUS NORVEGICUS) - Nurul Hidayah, Fitria; Nabawiyati Nurul Makiyah, Sri (Jurnal Kedokteran YARSI, 2005)
Honey is a special food because of the taste, nutrition, and high benefits of it. Honey?s effect to healing process also as well known already and has been reported, even the benefits of honey written in Holy Quran. Honey also has an antimicrobial effect because it produces hydrogen peroxide, nonperoxide component effect, acidity, immune system stimulation, and honey viscosity as the barrier against pathogenic bacteria. This scientific paper is presented to observe the stimulation of the effect of the immune system of honey in the lymph after the honey exposure. This research is observational, using experimental approach, which is done by using male white mice (Rattus norvegicus), with a body weight ± 220 gram, expose with honey for as long 35 days. The mice are divided into two groups, the control group and the treatment group. Each group consist of five mice. After the treatment, the mice are decapitated, and then the lymph are collected. The immune system activation in the lymph is estimated by measuring the white pulp diameter which will be compared between that of the treatment group and the control group. As the result of the observation, is obvious that the diameter of the white pulp in the treatment group is less than that of the control group. From the result of the statistical analysis, the significances counted 0,006 (p 0,05). It shows that there are significant differences between those two groups, and also proves that honey has indeed the effect to support the peripheral immune system.